2002
DOI: 10.1067/mva.2002.123762
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical testing for aortic endovascular grafts: Results of a Food and Drug Administration workshop

Abstract: The workshop raised awareness of significant performance issues and the challenges of modeling the extremely variable and relatively undefined environment of abdominal aortic aneurysms. Through the interactive format of the workshop, participants identified areas of preclinical testing, device design, and aspects of the simulated environment that need further consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The abdominal aorta also exhibited shortening and twisting deformation from the supine to fetal positions. Abel et al 12 suggested that durability tests and stress analyses for longitudinal and torsional loading and bending were some of the most critical areas needing improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abdominal aorta also exhibited shortening and twisting deformation from the supine to fetal positions. Abel et al 12 suggested that durability tests and stress analyses for longitudinal and torsional loading and bending were some of the most critical areas needing improvement.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Although government regulators have made significant efforts to improve preclinical evaluation of endovascular grafts, current testing protocols have not successfully predicted the aforementioned failure modes. 12,13 For designing preclinical tests, cardiac pulsation and respiratory motion have been the primary loading considerations in the form of pulsatile fatigue testing. On the other hand, static characteristics of the abdominal aorta, including the size and shape of the aortic neck, bifurcation divider offset, branch angle, and angular asymmetry, have been extensively investigated, since the geometry of the aorta is crucial for designing and implanting endovascular devices.…”
mentioning
confidence: 99%
“…The term "durability" has been used to describe the structural integrity of a device and its lasting ability to prevent the need for additional procedures. 21,22 Reporting these two issues separately is useful. The structural integrity of a device includes such events as stent fracture, fabric tears, and component separation.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Recognizing the need to improve preclinical testing, the FDA held a workshop in July 2001 attended by members of the medical device community involved in the development, testing, and use of EVGs. 9 The goal of the workshop was to define the physiological, anatomical, and morphological characteristics of abdominal aortic aneurysms (AAA) before and after EVG deployment and determine which characteristics should be considered during preclinical testing. Representatives of the EVG community agreed that there were significant limitations in testing and that the understanding of the in vivo environment was incomplete.…”
Section: First Workhop On Preclinical Testing Of Evgsmentioning
confidence: 99%